Information Systems for Real-Time Decisions: A Strategic Approach to Strengthening National Security and Economic Resilience - Dragomir-Constantin, Florentina-Loredana (The Journal of Accounting and Management, 2025)
The integration of circular economy indicators into decision-making processes with an impact on national security requires a rigorous conceptual foundation of three essential dimensions: real-time decision-making, circular supply chains, and economic and national security. These concepts are interdependent, articulated in a complex framework of sustainable and digital governance. In the current geopolitical context marked by instability, energy crises, and pressures on natural resources, the capacity of states to adopt rapid and efficient decisions becomes a critical element of economic resilience. This paper examines, through a quantitative analysis of data provided by EUROSTAT for the period 2010-2022, how two main indicators of the circular economy – the circular material use rate (CR) and the waste recycling rate (RW) – can underpin real-time decision-making processes, with implications for strengthening economic security. In this endeavor, information systems play a central role, facilitating the collection, processing, and analysis of data by applying clustering techniques (K-means) and identifying distinct patterns of circular performance among the Member States of the European Union. The results highlight the fact that the integration of circular indicators into decision-making flows, through advanced information systems, contributes significantly to increasing economic resilience and reducing systemic vulnerabilities. The development of autonomous circular chains, supported by digital decision-making technologies, underlines the importance of information systems as a strategic infrastructure for national security in a volatile global economic environment.